Mitogen‐activated protein kinase signaling in childhood asthma development and environment‐mediated protection. Issue 1 (14th September 2021) - Theodorou, Johanna; Nowak, Elisabeth; Böck, Andreas; Salvermoser, Michael; Beerweiler, Claudia; Zeber, Kathrin; Kulig, Paulina; Tsang, Miranda S.; Wong, Chun‐Kwok; Wong, Gary W. K.; Roponen, Marjut; Kumbrink, Jörg; et al.
Abstract: Background: While childhood asthma prevalence is rising in Westernized countries, farm children are protected. The mitogen‐activated protein kinase (MAPK) pathway with its negative regulator dual‐specificity phosphatase‐1 (DUSP1) is presumably associated with asthma development. Objectives: We aimed to investigate the role of MAPK signaling in childhood asthma and its environment‐mediated protection, including a representative selection of 232 out of 1062 children from two cross‐sectional cohorts and one birth cohort study. Methods: Peripheral blood mononuclear cells (PBMC) from asthmatic and healthy children were cultured upon stimulation with farm‐dust extracts or lipopolysaccharide. In subgroups, gene expression was analyzed by qPCR (PBMCs, cord blood) and NanoString technology (dendritic cells). Protein expression of phosphorylated MAPKs was measured by mass cytometry. Histone acetylation was investigated by chromatin immunoprecipitation. Results: Asthmatic children expressed significantly less DUSP1 ( p  = .006) with reduced acetylation at histone H4 ( p  = .012) compared with healthy controls. Farm‐dust stimulation upregulated DUSP1 expression reaching healthy levels and downregulated inflammatory MAPKs on gene and protein levels (PBMCs; p  ≤ .01). Single‐cell protein analysis revealed downregulated pMAPKs upon farm‐dust stimulation in B cells, NK cells, monocytes, and T‐cell subpopulations. Conclusion: Lower DUSP1 baseline levels in asthmatic children and anti‐inflammatory regulation of MAPK in several immune cell types by farm‐dust stimulation indicate a regulatory function for DUSP1 for future therapy contributing to anti‐inflammatory characteristics of farming environments.